MURDER Cooperative Learning Model through Edmodo Toward Mathematics Problem Solving and Motivation of Students - Putu Resya Adi Saputra; Sariyasa Sariyasa; I Nengah Suparta (Universitas Ahmad Dahlan, 2020)
MURDER cooperative learning model is based on cognitive theory that focuses on how humans acquire, embed, and process what they learn, as well as how the thinking and learning process occurs. This study aims to (1) determine whether the Edmodo-assisted MURDER cooperative learning model has a positive effect on students' problem solving ability and students’ motivation in learning mathematics (2) determine whether the Edmodo-assisted MURDER cooperative learning model has a positive effect on students' mathematical problem solving abilities (3) to determine whether the The MURDER cooperative learning model assisted by edmodo has a positive effect on students' motivation to learn mathematics. The research method used is a quasi experiment (quasi experiment) with the research hypothesis testing technique used is MANOVA. The experimental results show that (1) the problem solving ability and motivation to learn mathematics of students who take the Edmodo-assisted MURDER cooperative learning model is significantly better than problem solving ability and motivation to learn mathematics of students who take conventional learning, (2) the mathematics problem solving ability of students who following the Edmodo-assisted MURDER cooperative learning model is significantly better than the mathematics problem solving ability of students who take conventional learning, (3) the motivation to learn mathematics of students who take the Edmodo-assisted MURDER cooperative learning model is significantly better than the motivation to learn mathematics of students who take conventional learning .